2001
DOI: 10.1002/1615-9861(200109)1:9<1128::aid-prot1128>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Fasciola hepatica excretory-secretory products

Abstract: This paper describes a global investigation of the components of Fasciola hepatica excretory-secretory (ES) products by a proteomic approach. Despite the absence of a F. hepatica genome sequencing project we have shown that it was possible to identify 29 of the 60 prominent proteins found using two-dimensional gel electrophoresis. As well as cathepsin L proteases, a number of enzymes implicated in parasite protection from the host immune system were also found to be present in relatively large abundance. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 0 publications
3
80
0
6
Order By: Relevance
“…However, our study indicated it may be excreted or secreted into host serum (Table I); this result strongly argues against the possibility that SjFABP is unlikely to be accessible to the immune system (52). Furthermore the presence of FK506-binding protein in the adult worm ES proteome was also observed in Fasciola hepatica (29,30), S. bovis (33), and S. mansoni (34,35), suggesting that its secretion is conserved among trematodes. FABP from F. hepatica induces an immune response in mice that is protective to challenge infection with S. bovis cercariae (62), whereas FABP from S. mansoni induces immune protection against challenge with F. hepatica metacercariae and S. mansoni cercariae (62).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, our study indicated it may be excreted or secreted into host serum (Table I); this result strongly argues against the possibility that SjFABP is unlikely to be accessible to the immune system (52). Furthermore the presence of FK506-binding protein in the adult worm ES proteome was also observed in Fasciola hepatica (29,30), S. bovis (33), and S. mansoni (34,35), suggesting that its secretion is conserved among trematodes. FABP from F. hepatica induces an immune response in mice that is protective to challenge infection with S. bovis cercariae (62), whereas FABP from S. mansoni induces immune protection against challenge with F. hepatica metacercariae and S. mansoni cercariae (62).…”
Section: Discussionmentioning
confidence: 62%
“…Importantly this information can be expected to facilitate the discovery of vaccines and new therapeutic drug targets as well as new diagnostic reagents for schistosomiasis control. Proteomics approaches encompass the most efficient and powerful tools for identification of protein complexes and have been widely used to decipher the ES components of the filarial parasite Brugia malayi (19), Leishmania (Trypanosomatidae) (20), nematodes (21)(22)(23)(24)(25)(26), and Trematoda (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). For the genus Schistosoma, the ES compositions of S. mansoni have been identified in many developmental life stages, including sporocyst (34), cercaria (35,36), and egg (37) but have not been characterized in the adult worm.…”
mentioning
confidence: 99%
“…hepatica (24,(63)(64)(65)(66), C. sinensis (67), and O. viverrini (68). Approximately 65% of the proteins identified here were also detected in at least one of these flukes, but only enolase, actin, and triose-phosphate isomerase were identified in all three species.…”
Section: Transcriptome and Secreted Proteome Of Fascioloides Magnamentioning
confidence: 75%
“…These products include enzymes with important antioxidant functions (Jefferies et al 2001). Superoxide dismutase (SOD) catalyses the dismutation of superoxide radical to hydrogen peroxide and water, Catalase (CAT) catalyses the breakdown of hydrogen peroxide to oxygen and water, and Glutathione peroxidase (GPX) facilitates the destruction of both hydrogen peroxide and organic peroxides (Kidd 1997).…”
Section: Introductionmentioning
confidence: 99%